Las tareas escolares y su incidencia en el rendimiento académico de los estudiantes de Cuarto año de Educación Básica de la Unidad Educativa "Marco Aurelio Subía" de la parroquia Tanicuchí cantón Latacunga, en el periodo 2016-2017. - Aguaiza Iza, Myrian Elizabet (2018)
The present research work was developed under the premise of analyzing the incidence of school tasks in the academic performance from the children of the Fourth year of the Basic General Education of the Educational Unit "Marco Aurelio Subía- Batalla de Panupali", knowing the new ministerial provisions on sending homework to the students. The methodology used in the research is framed in a hypothetical method with the establishment of the negative impact of an excessive burden of homework, in order to examine the advantages, the disadvantages and the optimal and real conditions under which the student performs the homework, whence it is sought by the application of techniques and research tools that allow to know the current situation of the development of homework and academic performance of the students. From the theoretical revision that has been developed it has been possible to know that the homework constitutes an educational reinforcement, through which, the student practices and strengthens the learning that is acquired in the classroom. In the same sense, it is considered that through this educational reinforcement the student can improve the learning and therefore the academic performance. However, it is necessary for the structuring of the homework, the teacher must take into account the level of difficulty that is in accordance with the child's evolutionary period and with the contents that have been given in the classroom, the amount of time estimated for the accomplishment of the homework and the level of access to the information, in order to guarantee the optimal conditions for the performance of the homework to positively affect the school performance. From the research, it has been possible to conclude that parents need to be aware of the contents and methods of teaching, so that they can be an educational guide for the student.